2015
DOI: 10.1016/j.tiv.2015.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Benzo[a]pyrene-induced nitric oxide production acts as a survival signal targeting mitochondrial membrane potential

Abstract: Benzo[a]pyrene (B[a]P), the prototype molecule of polycyclic aromatic hydrocarbons, exhibits genotoxic and carcinogenic effects, which has led the International Agency for Research on Cancer to recognize it as a human carcinogen. Besides the well-known apoptotic signals triggered by B[a]P, survival signals have also been suggested to occur, both signals likely involved in cancer promotion. Our previous work showed that B[a]P induced an hyperpolarization of mitochondrial membrane potential (ΔΨm) in rat hepatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 47 publications
2
20
0
Order By: Relevance
“…In order to test whether the B[a]P-increased mitochondrial IF1 protein level was involved in both the glycolytic shift and cell survival signaling we recently reported 21, 22 , we decided to test the role of IF1 towards both glycolytic shift and cell death by using a siRNA approach. First, western blotting experiments were carried out in order to validate the siRNA targeting IF1 (siIF1) used.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In order to test whether the B[a]P-increased mitochondrial IF1 protein level was involved in both the glycolytic shift and cell survival signaling we recently reported 21, 22 , we decided to test the role of IF1 towards both glycolytic shift and cell death by using a siRNA approach. First, western blotting experiments were carried out in order to validate the siRNA targeting IF1 (siIF1) used.…”
Section: Resultsmentioning
confidence: 99%
“…S2C). Our previous work indicated that B[a]P metabolism by CYP1B1 could play a role in metabolism reprogramming 21, 22 . However, as for CH223191, α-naphthoflavone did not prevent IF1 increase.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations